2020
DOI: 10.3390/molecules25153533
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Huberantha jenkinsii and Their Biological Activities

Abstract: The phytochemical investigation of Huberantha jenkinsii resulted in the isolation of two new and five known compounds. The new compounds were characterized as undescribed 8-oxoprotoberberine alkaloids and named huberanthines A and B, whereas the known compounds were identified as allantoin, oxylopinine, N-trans-feruloyl tyramine, N-trans-p-coumaroyl tyramine, and mangiferin. The structure determination was accomplished by spectroscopic methods. To evaluate therapeutic potential in diabetes and Parkinson’s dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The α -glucosidase enzyme inhibition assay was carried out according to the method in our previous report [ 27 ]. The inhibitory activity was determined by measuring the p -nitrophenol, a yellow color substance that can be monitored at 405 nm, released from p -nitrophenyl-α-D-glucopyranoside ( p NPG) by the α -glucosidase enzyme.…”
Section: Methodsmentioning
confidence: 99%
“…The α -glucosidase enzyme inhibition assay was carried out according to the method in our previous report [ 27 ]. The inhibitory activity was determined by measuring the p -nitrophenol, a yellow color substance that can be monitored at 405 nm, released from p -nitrophenyl-α-D-glucopyranoside ( p NPG) by the α -glucosidase enzyme.…”
Section: Methodsmentioning
confidence: 99%
“…TCT α-glucosidase inhibitory activity, IC 50 , was 0.42 µM in Tribulus terrestris Linn. and 0.6 µM in Huberantha jenkinsii [66]. One study showed that TCT extract from Tribulus terrestris induced extrinsic, as well as intrinsic, apoptosis pathways in cancer cells [67].…”
Section: Other Small Molecular Constituentsmentioning
confidence: 99%
“…7 In addition, in our previous work, it has been proved that NCT isolated from Chinese yam (Dioscorea opposita Thunb.) has excellent hypoglycemic activity against αglucosidase (IC50 = 0.40 μM) 8 and its inhibitory activity on αglucosidase was even better than that of drug acarbose, 9 which can be used as a candidate drug to reduce blood glucose. However, its poor water solubility and stability limit its bioavailability.…”
Section: ■ Introductionmentioning
confidence: 99%